Adjusting fiscal balances for the business cycle New tax and expenditure elasticity estimates for OECD countries - Price, Robert (OECD Economics Department Working Papers, 2015)
This paper re-estimates the elasticities of government revenue and expenditure items with respect to the output gap for OECD countries. These elasticities are used by the OECD to calculate cyclically adjusted fiscal balances. The study updates the earlier 2005 study using the most recent datasets and tax codes, the coverage being confined in this paper to 35 countries, the 34 OECD member states and Latvia. The same two-step methodology is retained: revenue and expenditure elasticities with respect to the output gap being defined as the product of, first, the elasticities of individual revenue and expenditure items with respect to their bases and, second, the elasticities of these bases with respect to the output gap. A number of refinements and methodological improvements are made relative to the 2005 study. The revisions to individual elasticities relative to the 2005 vintage are significant in a number of cases but do not follow a clear pattern across countries, except for the elasticities of corporate income tax revenue which are revised up in most cases